2020
DOI: 10.1017/jns.2020.17
|View full text |Cite
|
Sign up to set email alerts
|

Early-life conditioning strategies to reduce dietary phosphorus in broilers: underlying mechanisms

Abstract: Abstract Chickens adapt to P and Ca restriction during the very first days of life by improving P utilisation efficiency. The present study was built to identify the mechanisms underlying this adaptive capacity, and to identify the optimal window of application of the restriction (depletion). A total of 1600 Cobb 500TM male broilers were used. During each phase (from age 0 to 4 d, 5 to 8 d, 9 to 18 d and 19 to 33 d), the animals received either a control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This allows an overall reduction in dietary P intake during the rearing phase. Depletion-repletion studies of growing animals such as pigs (8,10,136) and chickens (137)(138)(139)(140)(141) led to effectively increasing P utilization and limiting excretion without compromising animal well-being and performance. Some authors (9,142) have focused on improvements to bone health; these studies have led to better understanding of the deleterious effects of short-term dietary Ca deficits during growth on long-term bone mineralization.…”
Section: Depletion-repletion Strategymentioning
confidence: 99%
“…This allows an overall reduction in dietary P intake during the rearing phase. Depletion-repletion studies of growing animals such as pigs (8,10,136) and chickens (137)(138)(139)(140)(141) led to effectively increasing P utilization and limiting excretion without compromising animal well-being and performance. Some authors (9,142) have focused on improvements to bone health; these studies have led to better understanding of the deleterious effects of short-term dietary Ca deficits during growth on long-term bone mineralization.…”
Section: Depletion-repletion Strategymentioning
confidence: 99%
“…Furthermore, despite the differences in mineral levels, the expression of important functional genes, such as CALB1 and CALM2, remained unchanged, indicating the existence of mechanisms of compensation and adaptation to mineral utilization in chickens. This could help to mediate poultry health, mainly through mechanisms of long-term adaptive capacity, as has been suggested in broilers [75]. Finally, since mineral regulation mechanisms are not well described in laying hens' kidneys at molecular levels, our findings highlight the expression profiles of candidate genes in hens with advanced age, as well as their possible influence on production traits.…”
Section: Discussionmentioning
confidence: 51%
“…Although these genes are important for Ca and P regulation in the cell, the different levels of Ca/P provided in the diet did not influence their expression profile at 73 weeks of age, possibly because none of the levels used were considered deficient in the hens. Furthermore, these results could also be explained by diet adaptation since the laying hens received the same feed for a long time, indicating a compensation mechanism to maintain calcium absorption [75]. Probably, most of these genes would be differentially regulated in early ages when mineral renal physiology is more active [16].…”
Section: Discussionmentioning
confidence: 95%
“…The PPI network displayed 12 candidate DEPs interacting with all selected GO terms, pathways, and DEPs, especially SLC34A2, indicating that these DEPs participate in the regulation of Ca/P metabolism and homeostasis via different routes. Previous studies have proved that Ca/P intake in birds adapted by increasing the mRNA expression of Ca transporters such as ATP2B1, SLC34A2, and SLC30A1 [34][35][36]. It was also reported that the regulation of mineral homeostasis including Ca/P metabolism was reflected via altered mRNA abundances of FTH1, FTL, and SP1, which were involved in phospholipase C, calcium signaling, nuclear factor of activated T cell signaling, and immunomodulatory implications [37,38].…”
Section: Discussionmentioning
confidence: 99%